Saccharomyces boulardii Allows Partial Patients to Avoid Reusing Bismuth Quadruple for Helicobacter pylori Rescue Therapy: A Single-Center Randomized Controlled Study - Qu, Peng; Liu, Xiaoming; Xia, Xiujuan; Xie, Xiaoran; Luo, Ju; Cheng, Sha; Chi, Jingshu; Liu, Peng; Li, Huan; Zhao, Wenfang; Yang, Huihao; Xu, Canxia (Frontiers in Cellular and Infection Microbiology, 2022)
Background The increasing rate of drug resistance often leads to Helicobacter pylori (H. pylori) eradication failure and needs the rescue therapy. Thus, the exploration of new rescue therapeutic regimens is important. The present study was designed to test the beneficial effects of Saccharomyces boulardii (S.boulardii) prior to H. pylori rescue therapy basing on bismuth quadruple. Methods One hundred H. pylori-infected patients were randomly divided into two groups: study group and control group. Patients in the study group (n=50) underwent two-stages therapy: patients started with S.boulardii monotherapy for 2 weeks, and then tested for H. pylori infection after resting for 4 weeks without any therapy, patients who were still positive for H. pylori continued with bismuth quadruple eradication therapy. For the control group (n=50), all patients were observed and were not treated with any gastric drugs or antibiotics for 6 weeks, then those who were still positive for H. pylori received the same eradication therapy as the study group. Eradication rate, adverse events and the cost-effectiveness of two regimens were analyzed in this study. Results The H.pylori eradication rate of ITT (intent-to-treat) analysis and PP (per-protocol) analysis in the first phase of treatment were significantly higher in the study group than the control groups respectively (28.0% vs 2.0%, p<0.001 and 30.4% vs 2.1% p<0.001). For the total treatment effect, there were no significant differences in the eradication rate of ITT analysis (78.0% vs 80.0%) or PP analysis (90.7% vs 88.9%) between the study group and the control group. The cost‐effectiveness ratio of the study group was slightly higher than that of the control group (8.95 vs 8.55). There were two patients in the study group and four patients in the control group with the adverse events, respectively. There was no significant difference on the incidence of adverse events between the two groups (p=0.68). Conclusion S.boulardii may serve as a beneficial treatment option before H. pylori rescue therapy since it callowed partial patients to avoid reusing bismuth quadruple.